Fluorescent Carbon Dots as Prospective Nanoagents for Imaging-assisted Biomedical Applications - Phan, Le M. T. (Current Medicinal Chemistry, 2022)
Carbon dots (CDs), an emerging nanoagent providing an alternative to conventional fluorescent agents, are sparking the scientist’s interest in biomedical applications owing to their unique advantages, including ease of synthesis, large scale production, low cost, prominent photoluminescence, good photostability, easy functionalization, sufficient biocompatibility, good nanocarrier, and excellent ability to generate reactive oxygen species or heat. Herein, this perspective provides a viewpoint about imaging-assisted biomedical applications using fluorescent CDs regarding in vitro and in vivo bioimaging, imaging-assisted sensing, and imaging-guided therapy. The opinions about their potential and challenges in applicable biomedical applications are discussed to develop, further ameliorated CDs for their intense exploitation in diverse imaging-assisted biomedical applications.
Keywords: imaging-assisted sensing